JUAL BELI SURAT PAJAK GADAI: ANALISIS MENURUT PERSPEKTIF SYARIAH: The Sale of Pawn Broking Certificate: A Shariah Analysis - Mohamad, Shamsiah; Mahbubi Ali, Mohammad (Jurnal Syariah, 2017)
The sale of pawn broking certificate is one of long-existing phenomena in Malaysia. This raises the question on what is the real purpose of this kind of transaction and the position of Shariah towards this activity. The authors undertake this research to examine this activity and to comprehend the issue from the Shariah point of view. The authors employ both semi-structured interview and observation methods. The research found that this kind of transaction actually refers to the sale of pledged asset by the pledgor (pawner) in case he experiences financial difficulties to redeem his asset under pledge. The proceeds will be used to pay the debt as well as the storage fee. The excess of proceeds (if any) is the exclusive right of the pledgor while the asset, previously used as pledge, is owned by the broker who purchased the certificate. Therefore the authors concluded that this kind of transaction is allowed from the Shariah point of view as it does not in any way prevent the creditor to receive his right (receivable).